Detecção de pernas utilizando um sensor de varredura laser aplicada a um andador robótico - Schneider Junior, Valmir Antônio (2013)
This work is about the development of the Smart Walker designed in the Postgraduate Program in Electrical Enginnering of the Federal University of Espirito Santo (UFES). The goal of developing this device is to help people with mobility impairment, since it can be used for both rehabilitation support and functional compensation. First, a revision of the State of Art about human mobility support devices is shown, with special focus on walkers. In this group, there are smart walkers, which are a new category of walkers that integrate advanced robotics, electronics and mechanics technology. Following, the mechanical and electronic architecture used in this project is described. This work is focused on the leg detection method implemented on the Smart Walker. The developed method uses information about transitions found in laser scans to detect leg postures patterns and, through some features such as leg width and distance between legs, check if the found pattern corresponds to the user’s legs. This information is useful to evaluate the spatial-temporal evolution of the user. Also, the implementation of a controller for the device is described, which uses command signals generated using the leg detection information. Some evaluations performed show the validity of the methods implemented, whose data are useful for the walker control, user’s gait analysis and safety rules. Therefore, the main results of this work are in the electronics developed for the system, in obtaining a flexible platform of experimentation and evaluation of control strategies, and the development of a natural interface for the walker, using a laser sensor. These features facilitate the usage of the device by people with mobility residual potentials, helping them to walk with more independence and safety.